Impulse Control (Iowa NOC) In: Nursing outcomes classification (NOC): Iowa outcomes project. - Johnson M; Maas M (Impulse Control (Iowa NOC) In: Nursing Outcomes Classification (NOC): Iowa Outcomes Project, 1997)
SCOPE NOTE: Ability to self-restrain compulsive or impulsive behaviors. Use only as a specific Iowa Nursing Outcomes Classification. Copyright (c) 1997, Mosby-Year Book, Inc. CINAHL EDITORIAL SEARCH SUGGESTION: The term IMPULSE CONTROL (IOWA NOC) is used for indexing when articles specifically concern the term or research about the term. For citations that concern the general topic or topics related to the term, consider searching the subject headings: COMPULSIVE BEHAVIOR; OBSESSIVE-COMPULSIVE DISORDER.